Fascination and Social Togetherness--Discussions about Spice Smoking on a Swedish Internet Forum - Anette Kjellgren; Helena Henningsson; Christophe Soussan (SAGE Publishing, 2013)
Spice is a smoking mixture containing synthetic cannabinoids with psychoactive effects similar to herbal cannabis. It is sold on the Internet and has become popular among young people. The purpose of the present study was to investigate experiences of intoxication induced by Spice, as described on a Swedish internet-based discussion forum. A systematic search yielded 40 reports, which were analyzed using phenomenological method. A total of 7 themes (composed of 27 categories) emerged from the analysis: 1. Spice use as social ritual; 2. Social secretiveness; 3. Intoxication remarks; 4. Well-being and elation; 5. Altered perception of reality; 6. Fears and coping; 7. Unpleasant physical effects. The results show that smoking was a social activity mostly carried out in small peer-groups, and that the substances induced strong intoxication with both positive and negative effects. Despite fears and unpleasant effects, the intoxication was often considered fascinating and rewarding.